DEPARTMENT OF INFORMATION TECHNOLOGIES IN EDUCATION PROCESS MANAGEMENT - N. Struzhkin (Вестник университета)
In contemporary environment effective management of education process, including financial management, is one the most important tasks at government level. Reforms of higher education in Russia have tendency to establish major universities with large quantity of students and great variety of educational programs. This article presents approach to management in educational organizations built on information technologies rather than on functional automatization and describes basic management tools using under proposed approach. In the core of such approach there is an idea to transfer most of management functions from human to an automated system, which becomes a center of management activities while human stays as data provider, controller and decision maker.